2022
DOI: 10.1007/s00167-022-06887-7
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injections of platelet-rich plasma decrease pain and improve functional outcomes than sham saline in patients with knee osteoarthritis

Abstract: Purpose To compare the long-term clinical eicacy provided by intra-articular injections of either Pure Platelet-rich Plasma (P-PRP) or sham saline to treat knee osteoarthritis (KOA). Methods This prospective, parallel-group, double-blind, multi-center, sham-controlled randomized clinical trial recruited participants with KOA from orthopedic departments at nine public hospitals (ive tertiary medical centers, four secondary medical units) starting January 1, 2014, with follow-up completed on February 28, 2021. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 20 publications
0
28
0
2
Order By: Relevance
“…In a prospective study [2], three intraarticular injections at weekly intervals of PRP did not result in improvements in symptoms or joint structure at 12 months among patients with knee osteoarthritis. However, another recent study [7] found a better functional outcome of knee arthritis after three PRP injections. Concentrations of growth factors and cytokines vary depending on the donor’s age, health, and gender.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study [2], three intraarticular injections at weekly intervals of PRP did not result in improvements in symptoms or joint structure at 12 months among patients with knee osteoarthritis. However, another recent study [7] found a better functional outcome of knee arthritis after three PRP injections. Concentrations of growth factors and cytokines vary depending on the donor’s age, health, and gender.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vivo experiment in a KOA mouse model, PRP injection in the joint cavity was found to effectively reduce the catabolic activity of chondrocytes and slow down the rate of chondrocyte apoptosis [23]. In addition, researchers also that platelet-rich plasma can reduce pain and synovial thickness by regulating macrophage subtypes through experiments in a mouse OA model [24]; a number of clinical studies have also continued to report the therapeutic value of PRP for KOA [8][9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…Activated PRP can release a variety of growth factors, cytokines and related signaling molecules, making it useful in KOA therapy to promote cartilage repair and regulate the inflammatory response, etc [5][6][7]. PRP is divided into pure platelet-rich fibrin (P-PRF), leukocyte and platelet-rich fibrin (L-PRF), purified platelet-rich plasma (P-PRP), leukocyte and platelet-rich plasma (L-PRP), and in recent years P-PRP has been gradually applied to KOA [8][9][10][11]. Currently, most of the P-PRP used for clinical and research purposes are derived from autologous blood, but it is difficult to prepare autologous P-PRP for patients with blood disorders or frailty, so allogeneic PRP has come into being.…”
Section: Introductionmentioning
confidence: 99%
“…The PRP arm showed statistically significant improvements over sham in IKDC, WOMAC, and VAS out to 60 months. 196 …”
Section: Recommendations Regarding Regenerative Therapiesmentioning
confidence: 99%
“…The PRP arm showed statistically significant improvements over sham in IKDC, WOMAC, and VAS out to 60 months. 196 Although there has been much variation in treatment protocols and specifically the total number of PRP injections, the optimal number of PRP injections for positive outcomes has been under investigation. In 2019, one systematic review studied the clinical effectiveness of single versus multiple (double or triple) PRP injections for knee osteoarthritis.…”
Section: Recommendations Regarding Genicular Nerve Ablationsmentioning
confidence: 99%